2009
DOI: 10.1002/jnr.22052
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of oligomerization of expanded polyalanine repeat proteins

Abstract: Many human proteins contain amino acid repeats that can form homopolymeric amino acid (HPAA) tracts. HPAA tract proteins that contain polyalanine sequences promote diseases, including oculopharyngeal muscular dystrophy. The pathological properties of these proteins develop when the repeats match or exceed approximately 20 residues. We analyzed the oligomerization of yellow fluorescent protein (YFP) and GST fusion proteins containing >20 alanine repeats by using sucrose density gradient centrifugation. YFP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Therefore, we also tested the effect of an extension solely consisting of alanine residues, a strongly aggregation-prone sequence also implicated in human genetic diseases. 53 We found that an Ala extension was able to circumvent the need for p97 similar to what we observed for the V5-His sequence despite the fact that it caused the reporter to aggregate (Fig. 5a).…”
Section: Constraints Of Amino Acid Compositions Of Extended Peptidessupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, we also tested the effect of an extension solely consisting of alanine residues, a strongly aggregation-prone sequence also implicated in human genetic diseases. 53 We found that an Ala extension was able to circumvent the need for p97 similar to what we observed for the V5-His sequence despite the fact that it caused the reporter to aggregate (Fig. 5a).…”
Section: Constraints Of Amino Acid Compositions Of Extended Peptidessupporting
confidence: 64%
“…Notably, we confirmed that the UFD substrates with glycine and glutamine extensions were still degraded by the UPS albeit in a p97-dependent way. We noted that fusions with glycine and glutamine extensions were prone to aggregation, as reported previously, 53,54 and since protein aggregation can hinder proteasomal degradation, 45 we wondered whether their inability to bypass p97 could be attributed to protein aggregation. Therefore, we also tested the effect of an extension solely consisting of alanine residues, a strongly aggregation-prone sequence also implicated in human genetic diseases.…”
Section: Constraints Of Amino Acid Compositions Of Extended Peptidesmentioning
confidence: 90%
“…Expansion of the wild-type A14 polyA segment in FOXL2 resulted in mislocalization and aggregation in a length-dependent manner; expansions shorter than A19 were completely benign, but longer expansions were increasingly deleterious . YFP linked to A 23 or greater formed soluble oligomers that were trypsin-resistant and toxic to cells. , Moreover, A 23 segments were found to self-interact and oligomerize, but A ≤18 did not display any self-interaction . Konopka et al expanded yeast Pab1 (an RNA binding protein similar to PABPN1) from 8 to 13, 15, 17, and 20 alanines.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally expanded polyA segments have been linked to nine human diseases, eight of which result in congenital malformations, while the ninth, oculopharyngeal muscular dystrophy (OPMD), is an adult-onset disease. , The disease mechanisms are uncertain, but it is established that expansion of polyalanine tracts can lead to protein misfolding, aberrant protein–protein interactions, cellular mislocalization, and aggregation. , Several lines of evidence link the aggregation of proteins containing expanded polyA segments to toxicity. PolyA-fusion proteins form toxic aggregates, , and both aggregation and toxicity can be reduced by overexpression of ubiquitin. , Treatments that reduced aggregation of the protein implicated in OPMD, polyadenylate binding protein nuclear 1 (PABPN1), also reduced toxicity and morbidity. The solubility and toxicity of polyA within the context of a PABN1-like protein are strongly length-dependent, with a sharp transition around 20 alanines . As with other aggregation-related disorders, soluble oligomers are suspected to serve as intermediates in the aggregation process and to be more toxic than mature aggregates. , …”
mentioning
confidence: 99%
“…Likewise, mutations that expand poly(A) lengths to beyond a threshold of approximately 18 alanines lead to disease in nine different proteins (21). The poly(A) sequences crossing this disease-length threshold also lead to clustering into inclusions (22,23). Mutations in SOD1 that lead to amyotrophic lateral sclerosis are also associated with the formation of inclusions (24).…”
mentioning
confidence: 99%